Infinitely Many Solutions for Perturbed Hemivariational Inequalities. (6th December 2010) - D'Aguì, Giuseppina; Molica Bisci, Giovanni
Abstract : We deal with a perturbed eigenvalue Dirichlet-type problem for an elliptic hemivariational inequality involving thep -Laplacian. We show that an appropriate oscillating behaviour of the nonlinear part, even under small perturbations, ensures the existence of infinitely many solutions. The main tool in order to obtain our abstract results is a recent critical-point theorem for nonsmooth functionals.